THE CORRELATION BETWEEN MOTIVATION AND ACHIEVEMENT OF SIXTH YEAR PUPILS AT SDN INPRES 3 BIROBULI IN LEARNING ENGLISH - Sari Wulandari (Qalam : Jurnal Ilmu Kependidikan, 2018)
This research was a correlation study with two variables â€“ variable X standing for motivation and variable Y standing for achievement. The purpose of this study was to find out is there any positive correlation between motivation and achievement in leraning English especially for the pupils of grade six at SDN inpres 3 Birobuli. The data were collected by using documentation and questionnaire. Then, they were analyzed descriptively. Through questionnaire and pupilsâ€™ learning result, it was found that the level of correlation between variable X and Y was strong enough, there was positive correlation between variable X and Y since the value of r-counted (0,475) was higher than the value of r-table (0,235). Meaning the higher motivation they get the better achievement they have.Â